The Feeling of One’s Own in Terms of Inherent Community - Daujotytė-Pakerienė, Viktorija (Tautosakos darbai, 2016)
The article was presented as a paper at the seminar of the local culture studies. Here, on the grounds of the author’s personal experience and on the part of experience that reaches us from fiction, writers’ communication, and language, the meaning of one’s own is revealed. According to the author, the feeling of one’s own, or belonging, is an inherent, natural one; however, it transfers onto the level of consciousness. In Lithuanian cultural tradition, the concept of one’s own stems mostly from the family, testimonies of which are ample in the writers’ autobiographies and the life stories in general. Ideas by Vydūnas and Jonas Basanavičius support this statement. The sphere of one’s own is bridged by the language, which has a lot of words and concepts to describe it. The language remains directed at one’s own even in those cases when somebody becomes alienated from it, adopting another language instead. The possibility of returning is nevertheless there, which is originally described in the “Notes” by philologist Merkelis Račkauskas. Considering the importance of the concept of one’s own, the author maintains that deep tolerance and understanding or regard towards the other or foreign is more characteristic to the persons with keen feeling of “own”.